2014
DOI: 10.1080/15226514.2014.950410
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation Potential of Duckweed (Lemna minorL.) On Steel Wastewater

Abstract: An eco-friendly and cost effective technique- phytoremediation was used to remediate contaminants from waste water. This study demonstrated that phytoremediation ability of duckweed (Lemna minor L.) to remove chloride, sulphate from Biological Oxygen Treatment (BOT) waste water of coke oven plant. The BOT water quality was assessed by analyzing physico-biochemical characters--pH, Biological oxygen demand (BOD), Chemical oxygen demand (COD), total dissolved solids (TDS) and elemental concentration. It was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 27 publications
1
19
0
1
Order By: Relevance
“…The difference between groups was significant (Table 1). In accordance with our results, Saha et al (2015) reported that the phytoremediation technique has the capacity to reduce TDS levels in wastewater.…”
Section: Water Qualitysupporting
confidence: 92%
See 1 more Smart Citation
“…The difference between groups was significant (Table 1). In accordance with our results, Saha et al (2015) reported that the phytoremediation technique has the capacity to reduce TDS levels in wastewater.…”
Section: Water Qualitysupporting
confidence: 92%
“…Kashim and Singh (2002) reported that due to increase of pH, there was an increase in the uptake of elements. This is the reason that initially relative growth rate of treated plants significantly increased with the passage of time (Saha et al, 2015).…”
Section: Water Qualitymentioning
confidence: 98%
“…The essential elements of this study are Mg and and Zn (micronutrients) which possess higher BCF value for both roots and shoots and in TrF. This is due to the ability of plants to uptake essential elements compared to non-essential elements also plants may develop tolerance strategies that reduce their uptake and accumulation (Saha et al, 2015;Sarathambal et al, 2017;Sung, Lee and Munster, 2015). Plants which are possessing < 1 for TF and BCF values are considered to be unsuitable for phytoextraction process (Romanova, Shuvaeva and Belchenko, 2016;Romero-Hernández et al, 2017).…”
Section: Resultsmentioning
confidence: 98%
“…Plants which are possessing < 1 for TF and BCF values are considered to be unsuitable for phytoextraction process (Romanova, Shuvaeva and Belchenko, 2016;Romero-Hernández et al, 2017). Results indicate that the root parts of the plant possess high concentration of metal ions which indicates a higher accumulation of ions to protect photosynthetic tissue in the above ground parts (Saha, Banerjee and Sarkar, 2015;Salama, Al Watban and Al-Fughom, 2011). High concentration of metal ions in the root indicates that element compartmentalization, tolerance strategy by the plant in respect to the different metal ions and the level of concentration (Hazra et al, 2015;Zengin and Munzuroglu, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…They can grow naturally on calm waterways like abandoned rivers, canals and ponds [39]. Both of these plants are also able to absorb heavy metals found in wastewater [40][41]. This study aims to determine the tolerance and survival of these two plants (A. pinnata and L. minor) in treated POME as to select the right concentrations of POME to be used in the next stage of plant uptake in larger scale (pilot scale) by these plants in treated POME.…”
Section: Introductionmentioning
confidence: 99%